Representasi Human Interest Pada Foto Pemulung Anak-Anak Dalam Majalah Seratamata Edisi 1 - Alfreza Maurifa (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
This study aims to analyze the representation of human interest in photographs of child scavengers published in Seratamata Magazine Issue 1. The phenomenon of children working as scavengers is a social reality often found in urban areas and reflects social inequality and structural poverty. In visual media, photojournalism not only functions as documentation but also shapes public perceptions of social realities. This research uses a descriptive qualitative approach with Roland Barthes’ semiotic analysis. The primary data consist of photographs of child scavengers published in Seratamata Magazine Issue 1, which are analyzed as visual texts. Data were collected through documentation and literature study. The analysis was conducted through three levels of meaning: denotation, connotation, and myth. The results show that the photographs strongly represent human interest values through facial expressions, body language, and the landfill environment where the children carry out their activities. At the denotative level, the photos depict children collecting recyclable waste. At the connotative level, the images convey meanings related to life struggles, economic burdens, and social conditions that force children to work at an early age. At the myth level, the photographs represent structural poverty in urban society where childhood is not always associated with play and education. Thus, the photographs function not only as visual documentation but also as media that build empathy and social awareness toward the lives of child scavengers.This study aims to analyze the representation of human interest in photographs of child scavengers published in Seratamata Magazine Issue 1. The phenomenon of children working as scavengers is a social reality often found in urban areas and reflects social inequality and structural poverty. In visual media, photojournalism not only functions as documentation but also shapes public perceptions of social realities. This research uses a descriptive qualitative approach with Roland Barthes’ semiotic analysis. The primary data consist of photographs of child scavengers published in Seratamata Magazine Issue 1, which are analyzed as visual texts. Data were collected through documentation and literature study. The analysis was conducted through three levels of meaning: denotation, connotation, and myth. The results show that the photographs strongly represent human interest values through facial expressions, body language, and the landfill environment where the children carry out their activities. At the denotative level, the photos depict children collecting recyclable waste. At the connotative level, the images convey meanings related to life struggles, economic burdens, and social conditions that force children to work at an early age. At the myth level, the photographs represent structural poverty in urban society where childhood is not always associated with play and education. Thus, the photographs function not only as visual documentation but also as media that build empathy and social awareness toward the lives of child scavengers